Cyber Notary and Legal Certainty: Reconstructing the Role of Notaries in Digital Transactions in Indonesia - Muhammad Rizki Probo Nugroho (Program Studi Hukum Tata Negara, Fakultas Syariah dan Hukum Islam IAIN Bone, 2026)
The integration of information technology into notarial practice commonly referred to as cyber notary has encountered fundamental challenges within the Indonesian legal system, particularly due to normative tensions between the Law on Notarial Office, which requires physical presence, and the Law on Electronic Information and Transactions, which embraces digital flexibility. This study examines the extent of legal certainty afforded to digital deeds and seeks to reconstruct the role of notaries in ensuring the validity and authenticity of electronic transactions. This research employs a normative juridical method, utilizing statutory and conceptual approaches to critically reassess the function of notaries within Indonesia’s evolving digital transaction framework. The findings reveal that the absence of specific and technical regulatory instruments has resulted in a degradation of evidentiary strength, whereby digital deeds that should possess the status of authentic instruments are effectively equated with private deeds. Such regulatory gaps generate legal uncertainty that may impede the development of the digital economy. Accordingly, this study underscores the urgent need for a clear and integrated regulatory framework to optimize the notarial function in the digital era. It concludes that the traditional concept of physical appearance must be reconceptualized to encompass verified virtual interactions supported by stringent digital security standards. As a policy recommendation, the study advocates for regulatory harmonization through the adoption of integrated verification systems that strengthen the notary’s role in guaranteeing identity validity and the genuine intent of the parties in digital transactions.